Pembelajaran Behaviorisme dan Penerapannya dalam Pendidikan Biologi - Susanti, Dwi Kartika; Rais, Muh.; Susantina, Farida; Fannesia, Lisa Dwi; Akhmad, Megayana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Philosophy is an integral part of education, serving as its very foundation. Throughout history, various philosophical frameworks have emerged, including behaviorism. Despite some opinions that dismiss behaviorism as outdated in contemporary education, it possesses notable strengths alongside its weaknesses. Behaviorism is predicated on the idea that education involves changes in behavior, which can be achieved through guided repetition by educators. This approach offers advantages applicable to various subjects, including biology, as it addresses students' comprehensive competencies. Educators should selectively apply behaviorist principles in suitable learning contexts to maximize its benefits while mitigating its drawbacks.